MPFL Reconstruction With a Double-Loop Gracilis: The Concept of "Favorable Anisometry" - Etienne Deroche MD; Pieter Erasmus MBChB, MMed, FC; Cecilia Roberts MD (SAGE Publishing, 2022)
Background: Medial patellofemoral ligament (MPFL) reconstruction has shown very good results in patella dislocation and patient satisfaction. However, correct positioning and tensioning of the graft can be difficult to achieve and can lead to complications. Indications: Medial patellofemoral ligament reconstruction is always indicated for recurrent patellar instability with dislocation in extension, with or without other procedures that aim to correct predisposing factors of instability. Technique Description: An arthroscopic examination is first done to assess chondral lesions. The gracilis tendon is detached from the tibia and prepared to pass through 3-mm drill holes. The medial edge of the patella is exposed, and two 3-mm drill holes are made. Dissection is performed with a scissors between the second and third layers toward the medial epicondyle, where a small skin incision is made. A guidewire is placed just anterior and distal to the adductor tubercle. A suture is used to test the isometry of the femoral drill hole. If correct tension or "favorable anisometry" is achieved, a 5-mm bone anchor is placed. The graft is looped and pulled into the femoral hole with sliding sutures. The 2 free ends of the graft are pulled through the patellar drill holes and looped back onto themselves. The graft is tensioned with the knee in maximum extension while pulling the patella proximally with a bone hook as hard as possible in the direction of the femoral shaft. The principle is that with maximum quads contraction, the tension in the patella tendon should be more than in the reconstructed MPFL. Results: Immediate full range of motion, intensive isomeric quads contraction exercises, and full weight-bearing with crutches for 2 to 4 weeks are recommended. Sport can be resumed after 3 months, but it usually takes 6 months to play at the same level as before. Discussion/Conclusion: The technique of "favorable anisometry" of the MPFL has shown a very low rate of recurrence of patella dislocation. Complications are rare and extensor lag is very uncommon, thanks to the specificity of tensioning the graft. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.